EXPERT ASSESSMENT OF THE PERFORMANCE PARAMETERS OF A RETAILER - SEREDA, Serhii; SAPOZHNIK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers the issue of assessing the quality of retail trade services, which is caused by the ever-growing assortment and price competition between trade enterprises under conditions of a high level of consumer awareness of goods and services. It is noted that the efficiency of a retail trade enterprise, due to its specificity, is determined by the quality of services provided to the consumer. The models proposed for expert evaluation and comprehensive analysis of the efficiency of a retail enterprise using the parameters of service quality are analyzed. It is concluded that for a more complete assessment of performance, a retailer should take into account additional parameters on which consumers may not express their opinion, but which are necessary for the sustainable development of the enterprise and are important for other stakeholders: business partners, the State, and society. These parameters should characterize business processes in terms of their organization within the retail enterprise and should be assessed only by the service provider. An attempt to develop a scale for assessing the parameters of efficiency of retail trade enterprise is presented, based on the allocation of parameters for assessing the quality of services in accordance with the main directions of consumer perception of the quality of trade services. It has been proved that assessing the efficiency of a retailer’s activity according to the proposed parameters in the established periods of time allows top management to visualize the state of affairs at the enterprise and understand how efficiently it works. The possibility of using the evaluation scale of parameters before making managerial decisions to improve the competitiveness of retail trade enterprise on the basis of increasing the efficiency of the main areas of perception of trade services, the quality of which is assessed both directly by the buyer and the seller.